CARA SEDERHANA MENGELOLA KEUANGAN KELUARGA - Handayani, Nila (Universitas Negeri Medan, 2013)
ABSTRACT Family is the smallest unit of the society consisting of heads of household and some people who collected and living somewhere under a roof in a state of interdependence. Financial problems are a common thing experienced by young families, especially in the first years of married life. Not to mention the little soon be present among you and your partner. Kata Kunci : Keluarga, mengelola keuangan.